VOSLÍ MŮSTKY: THE BOOK OUT OF CONTEST - Novotný, Vladimír (Bohemica Olomucensia, 2020)
The text brings the author's biography of the regional writer Klára Gočárová and deals in detail with her trilogy Voslí můstky. It reveals the genre fusion and put Gočárová's texts in the context of tradition of humorous and memoir literature.
Keywords: humorous novel; regional literature; literary prizes; Klára Gočárová